2020
DOI: 10.3390/nu12020333
|View full text |Cite
|
Sign up to set email alerts
|

Very Low-Calorie Ketogenic Diet: A Safe and Effective Tool for Weight Loss in Patients with Obesity and Mild Kidney Failure

Abstract: Very low-calorie ketogenic diets (VLCKD) are an effective and increasingly used tool for weight loss. Traditionally considered high protein, ketogenic diets are often looked at with concern by clinicians due to the potential harm they pose to kidney function. We herein evaluated the efficacy and safety of a VLCKD in patients with obesity and mild kidney failure. A prospective observational real-life study was conducted on ninety-two patients following a VLCKD for approximately 3 months. Thirty-eight had mild k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 143 publications
(107 citation statements)
references
References 34 publications
7
95
0
5
Order By: Relevance
“…Even more recently, a systematic review and meta-analysis of 12 studies, including a total of 801 patients, highlighted significant improvements in body weight, BMI, and waist circumference after VLCKD [ 7 ]. Bruci et al have also recently reported similar results upon evaluating 92 consecutively obese patients undergoing VLCKD; among these individuals, after dietary intervention, body weight, BMI, and fat mass were significantly lower than at baseline [ 17 ].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Even more recently, a systematic review and meta-analysis of 12 studies, including a total of 801 patients, highlighted significant improvements in body weight, BMI, and waist circumference after VLCKD [ 7 ]. Bruci et al have also recently reported similar results upon evaluating 92 consecutively obese patients undergoing VLCKD; among these individuals, after dietary intervention, body weight, BMI, and fat mass were significantly lower than at baseline [ 17 ].…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, this dietary regimen is contraindicated in the case of kidney failure and moderate-to-severe kidney disease and all patients enrolled in our study were screened for renal function before starting VLCKD. However, a recent study suggests that under clinician supervision, this diet is an effective and safe tool against obesity that can also be used in patients with mild kidney failure (estimated glomerular filtration rate: 60–80 mL/min) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The strong connection between mental status and food behavior warrants first of all an accurately targeted psychological support in order to favor compliance to dietary treatments. However, some dietary manipulations including certain foods [34,35], food supplements [36,37], and dietary patterns [38][39][40][41][42][43] together with pharmacological treatment [44,45] have been shown to impact appetite and mood and/ or proved particularly beneficial in subjects with severe obesity and in post-bariatric patients. Such measures should be therefore taken into consideration in the next months in order to favor dietary adherence and metabolic improvement, leveraging a multidisciplinary approach to treat those severely obese seeking bariatric surgery and those who have lost weight but need lifelong follow-up after bariatric surgery [46].…”
Section: Discussionmentioning
confidence: 99%
“…71 Moreover, we previously showed that kidney function is not altered by VLCKD in patients with mild chronic kidney disease (GFR > 60), with almost one third even presenting GFR normalization after the dietary intervention. 10 Noteworthy, VLCKDs rely on meal replacements whose protein source is whey and plant derived, and, when gradual reintroduction of other protein sources occurs, fish, poultry and dairy are strongly recommended over red meat, with total protein intake being always equal to or lower than Recent stroke or myocardial infarction Preclinical evidence suggests ketone bodies to be protective on ischaemic brain and heart damage. No clinical data are available yet.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%